Prediction of emergency cerclage outcomes in women with cervical insufficiency: The role of inflammatory, angiogenic, and extracellular matrix-related proteins in amniotic fluid. - Kyong-No Lee; Kyo Hoon Park; Yu Mi Kim; Iseop Cho; Tae Eun Kim (PLoS ONE, 2022)
Objective We aimed to determine whether various novel inflammatory, angiogenic, and extracellular matrix-related mediators in amniotic fluid (AF) can independently predict emergency cerclage outcomes in women with acute cervical insufficiency (CI). Methods This was a retrospective cohort study conducted among 50 singleton pregnant women (18-25 weeks) who underwent emergency cerclage for CI and were subjected to amniocentesis. The AF samples were assayed for endoglin, endostatin, haptoglobin, insulin-like growth factor-binding protein (IGFBP)-3, -4, kallistatin, lumican, macrophage colony-stimulating factor (M-CSF), pentraxin 3, p-selectin, receptor for advanced glycation end products (RAGE), resistin, transforming growth factor beta-induced (TGFBI), and vitamin D-binding protein (VDBP) levels. Interleukin (IL)-6 levels in the AF were also measured for comparison with potential biomarkers assessed in this study. The primary endpoint was spontaneous preterm delivery (SPTD) at <34 weeks following emergency cerclage. Results The AF levels of pentraxin 3, RAGE, and resistin were significantly higher in women who had SPTD at <34 weeks after cerclage placement (pentraxin-3: P = 0.003; RAGE: P = 0.041; and resistin; P = 0.002). In multivariate analysis, elevated AF levels of pentraxin 3 (P = 0.007) and resistin (P = 0.006), but not those of RAGE (P = 0.069), were independently associated with the occurrence of SPTD at <34 weeks after cerclage, following adjustment for baseline clinical variables (e.g., cervical dilation). The area under the curve (AUC) values of AF pentraxin 3, RAGE, and resistin for the prediction of SPTD at <34 weeks were 0.749, 0.669, and 0.770, respectively, which were similar to those of AF IL-6. However, in univariate analyses, no differences in the AF levels of endoglin, endostatin, haptoglobin, IGFBP-3, IGFBP-4, kallistatin, lumican, p-selectin, TGFBI, and VDBP were found to be associated with SPTD at <34 weeks after cerclage placement. Conclusions In women with acute CI, the AF levels of pentraxin 3, RAGE, and resistin could be useful novel biomarkers for predicting SPTD following emergency cerclage. However, the clinical utility of these new biomarkers should be validated in larger multicenter studies.